A Validated Reversed-Phase HPLC Method for the Determination of Vildagliptin from Tablet Dosage Form - Khatun, Rahima; Mirazzunnabi, Md (International Journal of Pharmaceutical and Life Sciences, 2013)
A simple, rapid, precise and cost effective method has been developed and validated for determination of Vildagliptin in pharmaceutical tablet dosage form. The chromatographic separation was carried out with Shimpack VP-ODS, 150 × 4.6 mm, 5?m analytical column and mobile phase containing 0.02M phosphate buffer (pH 4.6) and acetonitrile at the ratio (80:20% v/v). pH of the buffer solution was adjusted with orthophosphoric acid. The instrumental settings include flow rate 0.7 ml/min, column temperature at 25ºC and detector wavelength of 210nm using a photodiode array detector. Theoretical plate for Vildagliptin was 6219 and tailing factor was 1.38. DOI: http://dx.doi.org/10.3329/ijpls.v2i3.15455 International Journal of Pharmaceutical and Life Sciences Vol.2(3) 2013: 90-98